Analysis of the Qur'an surah Al-Waqi'ah verses 7-56 based on a set perspective on mathematics - Huda, Yusri Kamilatul; Rahmasari, Tata; Loka, Suci Upita; Azizah, Richah Dian; Fitriani, Ulliya (Journal of Islam and Science, 2023)
Al-Qur'an is the guide of human life, which is the source of all knowledge. Unfortunately, in modern times, there are still many people who do not believe that. This study will examine one of the many surah in the Qur'an, namely Surat al-Waqi'ah based on a set perspective on mathematics. The aim is to dissect and prove that religious knowledge (al-Qur'an) can be integrated with science (mathematics). This study uses the library research method, namely the collection of sources or literatures relevant to the subject, such as books of the Qur’an interpretation, books of the set, and journal articles. The results show that on the last day, people will be divided into three groups or sets, namely the right set (A); the left set (B); and the set of the previous people (C). The set of the previous people is a subset of the right set, so the combination of A and C is A itself. While the right set (including the set of the previous people) is disjoint to the left set. The right set and the set of the previous people, they will find pleasure in heaven, while the left set will be tormented in hell.